Rola i zadania prokuratora w przesłuchaniu małoletnich świadków na podstawie art. 185a k.p.k. i art. 185b k.p.k. - Pawlik-Czyniewska, Joanna (Wydawnictwo Uniwersytetu Wrocławskiego, 2014)
The main issue of the article concerns the actual role of the public prosecutor in the interrogation of juvenile witnesses. The author’s analysis shows that the participation of the prosecutor in interrogations satisfies the adversarial principle, and, at the same time, guarantees correctness and completeness of the results of the interrogations, which directly affects the quality and efficacy of criminal proceedings.
Keywords: prokurator; przesłuchanie; świadek małoletni